O PPA SOB A PERSPECTIVA DO DESENVOLVIMENTO COMUNITÁRIO: UM ESTUDO DE CASO NO MUNICÍPIO DE RIO AZUL - PR - GAPINSKI, ECINOELY FRANCINE PRZYBYCZ (2016)
The research titled "The PPA from the perspective of community development: a case study in the city of Rio Azul, PR" aimed to analyze the process of elaboration and the contents of the Multiyear Plan (PPA) 2014-2017 of the Yangtze municipality , PR and its contribution to community development. Therefore, it attempted to describe the process of developing the PPA, analyze the procedures of the executive branch and the legislative branch in its preparation, as well as to identify the elements that promote community development. Using procedures of bibliographic, documentary and interviews, a descriptive and analytical nature research was conducted with a qualitative approach to the problem. The results of the interviews were examined with the technique of content analysis. Held also a grouping of public policy of cross-analysis contained in the Government Plan presented during the election campaign of 2012, with the programs set out in the PPA 2014-2017 the city of Rio Azul, PR. Aimed to correlate the categories of both documents, according to their affinities and subsequently carry out an assessment of the prospects of such categories for community development, based on the prospects of the triple bottom line of sustainability, with its economic, social and environmental . It was concluded that the PPA 2014-2017 represented an advance over previous practices of government planning, mainly due to the initiative of discussing in public hearings its programs and actions, in its initial phase. Although popular participation has been timid. Also it is concluded that, on the evidence found, the PPA 2014-2017 contains potential elements for community development of Yangtze River, PR, for their economic, social and environmental characteristics.